Changes in several blood minerals after maximal fast incremental exercise in young table tennis players - Vitkiene, I.; Stasiulis, A.; Bogusas, V.; Kusleikaite, M. (Education. Physical training. Sport, 1999)
The purpose of this study was to examine the influence of standard fast incremental exercise on plasma concentrations of several blood minerals. Table tennis players (n=5, age: 14-17) participated as subjects in this study. Each subject performed an increasing work load (25 W every min) until exhaustion on electrically braked cycle ergometer. The initial work load was 50 W. Venous blood samples were taken before and immediately after the incremental test. Blood Zn, Cu, Mn, Fe, Mg and Ca concentrations were determined using atomic absorption spectrophotometry method. The significant (p<0.05) decrease in mean Cu and Mg blood concentrations was observed after fast incremental test in the investigated group. On the other hand the blood concentration of Mn and Zn showed the tendency to decrease and that of Fe and Ca to increase, but these changes were not statistically significant. The great intraindividual variation in the amount and direction of blood minerals changes was noticed. In conclusion, our and other studies data about acute blood minerals changes in response to exercise remain equivocal and their reasons remain to be established.